Effectiveness of Guided Inquiry-based Interactive Power-Point Learning Media on Electrolyte and Non-electrolyte Solution Materials for Class X SMA - Nuranisah Nuranisah; Syamsi Aini (Universitas Lampung, 2022)
Abstract: Effectiveness of Guided Inquiry-based interactive Power-Point learning Media on Electrolyte and Non-electrolyte Solution Materials for Class X SMA.Effectiveness of Interactive Power-Point Learning Media based on Guided Inquiry on Electrolyte and Non-electrolyte Solution Materials for class X SMA. This study aims to determine the level of effectiveness of guided inquiry-based interactive Power-point learning media on improving student learning outcomes in class X SMA Adabiah 2 Padang. This Research is carried out in April 2022- May 2022. The type of research used is quasi-experimental research. The instrumental used in the study was a test in the form of 20 multiple-choice questions that had validity, difficulty index, distinguishing power and Reliability with good question criteria. The Effectiveness level of Interactive Power-Point Learning Media based on guided inquiry is seen from the N-Gain test.